Application of CAD Technology in Extracting Line Feature of Industrial Part Image. (24th September 2022) - Li, Fei
Abstract : In order to solve the problem that the properties of the acquired images in engineering are often poor and the features of the images are seriously lost, so that the image features cannot be effectively developed, an application method of CAD technology in the extraction of linear features of industrial parts images is proposed. Based on 3D computer-aided design (CAD) data, by solving the parameter transformation relationship between the CAD 3D Cartesian coordinate system and the image coordinate system, the target line feature is projected onto the image, and the initial value range of the image line feature is obtained. The edge point sequence is extracted by multiplication template matching, and the generated point sequence is fitted by the least square method to obtain the line equation of the image line feature. By solving the intersection of the intersecting lines of the image, the straight line segment representing the contour of the industrial part can be obtained with high precision. The experimental results show that the above algorithm is used to extract the line features of real industrial part images, and the median error of the difference between the reconstructed line length and the line length measured by the vernier caliper is 0.232 mm. The practice has proved that CAD technology has a certain auxiliary and guiding role in the research of industrial part image feature extraction algorithms. It can be applied to high-precision image measurement and reverse engineering of regular industrial parts. In engineering technology, it can help improve the automation level of industrial production.